Vibration Analysis of Tapered Pole Linear Switched Reluctance Machine - Lenin N C; Arvind S V (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
The Vibration is one of the major problem in linear switched reluctance motors (LSRMs). This paper present a detailed analysis of vibration in a two phase LSRM and proposes a new structure to reduce the effect. The experimental results of this paper prove that the proposed structure is well suited for conveyor application.